2005
DOI: 10.3732/ajb.92.11.1853
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression in perennial Lychnis viscaria (Caryophyllaceae): effects of population mating history and nutrient availability

Abstract: We studied inbreeding depression in a perennial plant, Lychnis viscaria, in three populations differing in their inbreeding history and population size by measuring several traits at two nutrient levels over the plant's life cycle. The observed levels of inbreeding depression (cumulative inbreeding depression, from -0.057 to 0.629) were high for a plant with a mixed mating system. As expected, the population with a low level of isozyme variation expressed the least inbreeding depression for seed germination. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 66 publications
4
24
0
Order By: Relevance
“…In the A. pubescens population MP, significant inbreeding depression was expressed between seed production and seedling establishment (53%). Our result of high expression of inbreeding depression at these earlier life-history stages is consistent with results from many other plant species (MitchellOlds and Waller 1985;Charlesworth and Charlesworth 1987;Dudash 1990;Waser and Price 1991;Husband and Schemske 1996;Culley et al 1999;Kittelson and Maron 2000;Hull-Sanders et al 2005;Mustajärvi et al 2005). Similarly, Montalvo (1994), using an experimental approach, found expression of inbreeding depression to be high at seed germination and at seedling establishment in A. coerulea.…”
Section: Timing Of Expression Of Inbreeding Depressionsupporting
confidence: 92%
“…In the A. pubescens population MP, significant inbreeding depression was expressed between seed production and seedling establishment (53%). Our result of high expression of inbreeding depression at these earlier life-history stages is consistent with results from many other plant species (MitchellOlds and Waller 1985;Charlesworth and Charlesworth 1987;Dudash 1990;Waser and Price 1991;Husband and Schemske 1996;Culley et al 1999;Kittelson and Maron 2000;Hull-Sanders et al 2005;Mustajärvi et al 2005). Similarly, Montalvo (1994), using an experimental approach, found expression of inbreeding depression to be high at seed germination and at seedling establishment in A. coerulea.…”
Section: Timing Of Expression Of Inbreeding Depressionsupporting
confidence: 92%
“…In three populations of Lychnis viscaria , ID in the number of leaves was increased by fertilization, though the pattern was less clear for ID in cumulative fitness in the second year, which differed among populations (Mustajärvi et al. ). However, ID does not always increase with nutrient supply.…”
Section: Discussionmentioning
confidence: 99%
“…Among early fitness traits, we found a positive correlation between seed mass and germination in the seeds harvested from the tested crosses (seed mass 2, germination 2). There were no Loeschcke, 1994, 1995;0.91 under drought stress: Hauser and Loeschcke, 1996) and Lychnis viscaria (up to 0.629; Mustajärvi et al, 2005), but also for species from other plant families, for example the lily Bulbine bulbosa (0.85; Owen et al, 2007) or Magnolia obovata (up to 0.69/0.97; Ishida, 2006).…”
Section: Among-family Variance In Idmentioning
confidence: 99%
“…The degree to which inbreeding affects fitness traits of different life stages differs between species that are predominantly selfers and species that are predominantly outcrossers (Husband and Schemske, 1996;Ouborg et al, 2006). There is a tendency of selfing species to suffer more severe ID in late life-cycle traits compared with early traits, whereas outcrossing species tend to suffer more severe ID in early traits (for example Mustajärvi et al, 2005). Husband and Schemske (1996) suggested that the ID in early traits is caused by recessive lethals, which are effectively purged through inbreeding, whereas ID in late traits is caused by recessive and only mildly deleterious mutations that are very difficult to purge even in highly inbred populations.…”
Section: Introductionmentioning
confidence: 99%